Uang Gandong and the Validity of Islamic Marriage in Waemangit Village - Nursalima Yoisangaji (IAIN Parepare, 2026)
This study examines Uang Gandong, a customary wedding practice in Waemangit Village, Buru Regency, as a site of negotiation between Islamic law, maternal authority, and legal pluralism. The problem addressed in this article concerns the extent to which a local tradition that grants authority to the bride’s mother can be accommodated within Islamic marriage law without altering the pillars and requirements of marriage. This study aims to describe the practice, meaning, and social function of Uang Gandong, and to analyze its legal status through the concept of ‘urf. Using qualitative research with an empirical juridical approach, data were collected from seven purposively selected informants through observation, in depth interviews, and documentation. The data were analyzed using the Miles and Huberman model through data reduction, data display, and conclusion drawing. The findings show that Uang Gandong is given to the bride’s mother in the form of cash or a shroud as recognition of her maternal role in pregnancy, birth, care, and upbringing. Although the mother has authority to determine the amount or form of the gift, negotiation remains possible by considering the groom’s financial capacity. In Islamic law, Uang Gandong may be classified as ‘urf sahih when it functions as respect, does not impose hardship, and does not affect the validity of the marriage contract. However, it may become ‘urf fasid when it is treated as an absolute condition that delays or prevents marriage. This study recommends that Uang Gandong be maintained as a flexible customary tribute, not as a determinant of marriage validity.